De novo gene birth and the conundrum of ORFan genes in bacteria - uz-Zaman, Md. Hassan; Ochman, Howard (Genome Research, 2025)
Bacterial genomes are notable in that they contain large numbers of lineage-restricted (“ORFan”) genes, which have been postulated to originate from either horizontal transfer, rapid divergence from pre-existing genes, or de novo emergence from noncoding sequences. We assess the body of research that explores each of these hypotheses and demonstrate that the mystery of the origin of bacterial ORFans still remains unresolved. Nonetheless, bacteria offer several unique avenues for research into the process and mechanics of gene birth at a resolution not feasible in other organisms. Both their amenability to experimental evolutionary analysis and their strain-level variation in gene content foster investigations of how noncoding sequences acquire expression and transition into functionality—questions central to the origin of phenotypic novelty.